Comparação de diferentes cruzamentos comerciais de suínos e mtDNA associados às características de qualidade de carcaça e da carne - Cesar, Aline Silva Mello (2010)
The arms of this work were to compare the quality of carcass and meat as pH after 24 hours (pH24h), fat thickness (ET), percentage of drip loss (PDL), percentage of lean (PCM), color and percentage of intramuscular fat (PGIM) between two maternal lines of different racial composition, and verify the effect of crossover and knowledge of SNPs in the mtDNA D-loop region that characterize the cytoplasmic origin Asian or European in four different crossed commercial lines of pigs (AI, AII, BII, CII). One hundred forty four right half-carcasses of pigs were used for the study between two maternal lineages (A and B) and 288 to study the effect of crossing and cytoplasmic origin. The animals were slaughtered at live weight of 108 kg, and after 24 hours of slaughter data were collected for pH and ET from carcasses and samples were collected for analysis of color, PDL, PGIM and DNA extraction. For the characterization of animals and their mtDNA was performed a PCR-RFLP using the restriction enzyme ApoI, and by running a electrophoresis on 2% agarose gel containing ethidium bromide. The bands were recorded on laser scanner FLA 3000G (Fuji Film Co.). The results were submitted to analysis of variance in a completely randomized design with a significance level of 5% and means compared by using the program BioEstat 5.0 and SAS (2004). The characteristics of ET, PCM and pH24h showed a significant difference (p <0.05) between maternal lineages and between the crosses studied. It can be concluded that this work had no effect of maternal lines and the crosses on the carcass quality and meat studied, but were not influenced by mtDNA genotypes studied.